1984
DOI: 10.1177/002234338402100404
|View full text |Cite
|
Sign up to set email alerts
|

Military Spending and Economic Growth in the OECD Countries

Abstract: Cross-national comparisons of industrialized countries indicate that countries with a high defense burden (military spending as a share of GDP) tend to have lower rates of economic growth than do countries with a low defense burden. On the other hand, longitudinal data for several industrial countries indicate that economic growth is higher in periods with a high defense burden. This study attempts to overcome this apparent contradiction by pooling cross-sectional and longitudinal data within the framework of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1
3

Year Published

1986
1986
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(56 citation statements)
references
References 7 publications
6
46
1
3
Order By: Relevance
“…The impact of warmongering on the economy and investors' sentiment is potentially immense. Some researchers, such as Deger and Smith (1983) or Cappelen et al (1984), documented that large military expenditure retards economic growth and investment. These findings seem to hold for both OECD and less developed countries.…”
Section: Wars and International Political Crisesmentioning
confidence: 99%
“…The impact of warmongering on the economy and investors' sentiment is potentially immense. Some researchers, such as Deger and Smith (1983) or Cappelen et al (1984), documented that large military expenditure retards economic growth and investment. These findings seem to hold for both OECD and less developed countries.…”
Section: Wars and International Political Crisesmentioning
confidence: 99%
“…Faini et al (1984), Chan (1988), Antonakis (1997), Heo and DeRouen (1998) and DeRouen (2000) are among those carry out a time-series analysis. Whereas, Cappelen et al (1984), Landau (1986, Lipow and Antinori (1995), Blomberg (1996), Stroup and Heckelman (2001), Kollias et al (2007), Yakovlev (2007), apply a cross-country time series model. Furthermore, some studies consider relatively more homogenous samples.…”
Section: Review Of the Studies Included In The Meta Analysismentioning
confidence: 99%
“…Furthermore, some studies consider relatively more homogenous samples. These are studies by Cappelen et al (1984) and Landau (1996), in which both use a sample of OECD countries and Kollias et al (2007) concentrates on EU countries. Gyimah-Brempong (1989) and Dunne and Mohammed (1995) particularly look at a sample of African countries rather than a general of sample LDCs.…”
Section: Review Of the Studies Included In The Meta Analysismentioning
confidence: 99%
“…Literature Review:-The literature on military spending and economic growth dated back to the seminal work by Benoit (1973) Conversely, other studies conclude that heightened military spending exerts a negative relationship with economic growth due to a tendency to crowd out investment and the wider impacts of tax increases that are often necessary to finance the new expenditure (Smith, 1980;Cappelen et al, 1984;Dunne et al, 2001). Furthermore, other studies found that the relationship between military expenditure and economic growth might be mixed, such as (Chowdhury, 1991 Moreover, even where defense expenditure exerts a positive relationship with economic growth, it may nonetheless prove to a sub-optimal means of economic stimulation due to the greater effect exerted by non-military expenditure (Batchelor et al, 2000;Shieh et al, 2002).…”
Section: Issn: 2320-5407mentioning
confidence: 99%